Erosive oesophagitis: outcome of repeated long term maintenance treatment with low dose omeprazole 10 mg or placebo. Issue 4 (1st October 1998) - Bardhan, K D; Cherian, P; Vaishnavi, A; Jones, R B; Thompson, M; Morris, P; Brooks, A; D'Silva, J; Gillon, K R W; Wason, C; Patterson, J; Polak, J; et al.
Abstract : Aims —To investigate the efficacy of daily maintenance treatment with omeprazole 10 mg in reducing the relapse rate of healed erosive oesophagitis. Methods —Three hundred patients with erosive oesophagitis (grade 2 or greater) received omeprazole 20 mg daily for 12 weeks, followed by 40 mg daily for a further 12 weeks if required. After healing, patients were randomised to double blind treatment with omeprazole 10 mg daily or placebo for up to 18 months. On relapse the treatment cycle was repeated. Results —The cumulative healing rate at 12 weeks in the initial healing period was 95%, and 96% and 98% on rehealing courses after relapse in the first and second maintenance periods respectively. After 12 weeks of treatment, 98% of patients were free from heartburn and 97% were free of all reflux related symptoms. Relapse in the subgroup of patients who relapsed in both maintenance periods was infrequent on omeprazole 20 mg daily: only 9% at two years. Gastrin concentrations rose above normal in one third of patients. One patient had linear hyperplasia of endocrine cells and another had micronodular hyperplasia. There were no side effects definitely attributable to omeprazole. Conclusion —Maintenance treatment with omeprazole 10 mg daily keeps about 60% of patients with erosive oesophagitis in prolonged remission. Patients relapsing once are likely to do so again; they can subsequently be treated effectively with omeprazole 20 mg daily.